Contribuição ao estudo da atenção médica em Pronto Atendimento aos pacientes portadores do Vírus da Imunodeficiência Humana no Hospital das Clínicas da Universidade Federal de Minas Gerais, Pronto Socorro clínico referencial da região metropolitana de Belo Horizonte. - Cecilia Gomez Ravetti (2008)
Brazil has a specific system of primary health care to patients with HIV / AIDS. The introduction of highly active antiretroviral therapy allowed an increase in survival of these patients, making immunodeficiency entity of chronic coexistence. This study aims toprospective analysis of the causes that lead the patients with HIV / AIDS to seek emergency care in the Emergency Room of the Hospital das Clínicas da UFMG, referential hospital in the metropolitan region of Belo Horizonte. Methods: We studied in the period from 01/06/2006 to 31/05/2007, all adult patients with HIV, admitted consecutively in the Emergency Room of Hospital das Clínicas da UFMG. Results: We studied 99 patients who perform 118 admissions. The average age was 39.4 years (SD = ± 9.1). The relation between man and woman was 1,35:1. Regarding color and marital status, 27.3% were black, and 50% were singles. The most common form of transmission was heterosexual (18.2%). The time elapsed since the diagnosis and admission was between 0-5 years in 40.4% of cases. Most patients were admitted once. 55.1% of cases were under clinical follow up at some reference centre of care for patients of HIV / AIDS. The antiretroviral therapy and chemoprophylaxis was adequate in 56.8% and 29.7% of patients, respectively, in the admission of Emergency Room. The count of CD4 Tlymphocytes were below of 200 cel/mm3 in 45.7% of patients. There was no statistically significant difference, as the value of the count of lymphocytes T CD4 and the use of chemoprophylaxis for opportunistic infections depending on the outcome death (p = 0.2 and p= 1, respectively). The most frequents symptoms were increased body temperature (46.6%), diarrhea (30.5%), cough (28.8%), dyspnea (21.2%), headache (10.6%), nausea (10.6%) and vomiting (10.6%). The respiratory tract was the most affected, followed by gastrointestinaland neurological. There was no statistically significant difference between the affected system and outcome death. The opportunistic diseases most frequently diagnosed were: pneumocystosis (17.8%), Community acquired pneumonia (16.9%), diarrheal syndrome(16.1%) and oral candidiasis (10.2%). The demand for admissions represented 2.8% of admissions, with an average time of 4.6 days of stay in the Emergency Room. Conclusions: The patients seeking emergency care clinician had, in its majority, lymphocyte count of TCD4 low, almost half not used to HAART. There was a trend of the feminization ofHIV / AIDS. The diseases related to AIDS continue to be the most frequent in our environment, despite Brazil have specific high quality medical service for patients with HIV / AIDS.